Fabrication SiO2 -NiO foam via replication technique for steam methane reforming catalyst at low temperatures - Muda, Rizamarhaiza (2021)
Porous ceramic is a type of material that has highly open and partially interconnected pores. It has a wide range of applications, which include catalyst support, filtration, adsorption and separation.The aim of this study is to fabricate Silica-Nickel Oxide (SiO2-NiO) foams in the range 70 μm to 150μm open pore size, 75% to 90% of porosity, good physical and mechanical properties as a criteria catalyst in the Steam Methane Reforming (SMR) application. In this work, the porous foam fabricated with different compositions of SiO2 as derived from Rice Husk Ash (RHA) (20% to 35%) and at different sintering temperatures (850°C to 1250°C) by using replication sponge method. Characterisation of SiO2 and SiO2-NiO foams included morphological analysis, porosity and density test, and compression test as criteria compatibility of SiO2 and NiO as a catalyst in methane reforming. The morphology result showed open pores with size ranging from 15.13 μm to 76.06 μm. The lowest result for apparent porosity obtained was 65% and the highest was 81.74%, while the lowest and highest values for bulk density were 0.626 g/cm3 and 1.070 g/cm3, respectively. The result for compressive strength was within the range of 0.06 MPa to 0.47 MPa. Throughout the observations, the maximum performance shown the SiO2-NiO foam produced with 35wt% SiO2 and 5wt% NiO was found to have mechanical and physical properties much like those of a filter catalyst in SMR. The methane (CH4) conversion using the SiO2-NiO foam was shown the range of 34.72% to 42.6% at different low temperatures. The results proved that the foam from silica as derived from RHA and NiO is very suitable to be used as a catalyst in SMR due to achieved the minimum CH4 conversion over than 21%.